APPLICATION OF URBAN METABOLISM CONCEPT TO STUDY THE RESOURCE CONSUMPTION AND WASTE GENERATIONS OF SHOPPING MALLS AND OFFICE BUILDINGS IN THE FUTURE JURONG DISTRICT - LEOW MEI LING ADELINE (2013)
Bachelor's